2020
DOI: 10.1128/aac.00345-20
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationary Pharmacokinetics of Caspofungin in ICU Patients

Abstract: Standard dosing of caspofungin in critically ill patients has been reported to result in lower drug exposure, which can lead to subtherapeutic AUC0–24/MIC ratios. The aim of the study was to investigate the population pharmacokinetics of caspofungin in a cohort of 30 ICU patients with a suspected invasive fungal infection, with a large proportion of patients requiring extracorporeal therapies including ECMO and CRRT. Caspofungin was administered as empirical antifungal therapy 70 mg i.v. on the first day and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…Märtson et al ( 25 ) proposed a weight-based dose regimen for caspofungin. However, several other studies ( 26 , 31 33 ) have found no significant effect of weight on the pharmacokinetic parameters of caspofungin, similar to our research. Our study had a small sample size and a small range of changes in body weight.…”
Section: Discussionsupporting
confidence: 91%
“…Märtson et al ( 25 ) proposed a weight-based dose regimen for caspofungin. However, several other studies ( 26 , 31 33 ) have found no significant effect of weight on the pharmacokinetic parameters of caspofungin, similar to our research. Our study had a small sample size and a small range of changes in body weight.…”
Section: Discussionsupporting
confidence: 91%
“…This is essential for fungal infections because fungi, mainly Candida spp., colonize the mucosal surface [ 67 ]. Therefore, a certain degree of permeation and retention of the drug in the tissue is necessary without reaching or exceeding systemic therapeutic levels, C min = 3.55 µg/mL and C max = 11.73 µg/mL [ 68 , 69 , 70 ]. Porcine and human vaginal mucosas are substantially similar.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated permeation kinetics parameters and CSP retained amount are reported in Table 4 . Taking into account an application surface area of 62.8 cm 2 for the vaginal cavity [ 74 ], and a plasmatic clearance ( Cl p ) of 0.55 L/h [ 68 , 69 , 70 ], the theoretical human plasmatic steady-state concentration ( Cl ss ) that CSP would achieve was also calculated, being 1.65 ± 0.01 μg/mL, 0.95 ± 0.22 μg/mL and 1.43 ± 0.12 μg/mL for CSP-CTS, CSP-P407 and CSP-CTS/P407, respectively. Therefore, no systemic side effects related to the use of CSP are expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A case report (22) observed that the standard dose of caspofungin failed to reach the target plasma concentration level during ECMO support. However, other in vivo studies (23)(24)(25) have suggested that ECMO does not affect the pharmacokinetic characteristics of caspofungin. Caspofungin is hydrophilic (log P −2.798) but has a high protein binding rate (97%), which may lead to significant differences in its recovery in different types of ECMO circuits.…”
Section: Discussionmentioning
confidence: 96%